An Integrative Analysis of the Value-Belief-Norm Model and Theory of Planned Behavior in Enhancing Digital Donation Intention and Behaviour in Indonesia - Tri Antoro Adi; Didik Junaidi Rachbini; Erna Sofriana Imaningsih; Mas Wahyu Wibowo (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2026)
This study examines the determinants of digital donation behavior among Generation Z in DKI Jakarta by integrating the Value-Belief-Norm (VBN) theory and Theory of Planned Behavior (TPB) into a single structural model. This study uses survey data collected from 400 respondents selected through purposive sampling, analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Results reveal that altruistic values, egoistic values, and subjective norms significantly influence intention to donate, while biospheric values operate indirectly through attitude formation. Subjective norms emerge as the strongest predictor of attitude towards donation, reflecting the collectivist character of Indonesian society. Perceived behavioral control does not directly affect donation intention but significantly shapes positive attitudes toward donation. Attitude towards donation and intention to donate are confirmed as significant mediators within the integrated model. Findings of this study suggest that digital philanthropy campaigns targeting Generation Z should prioritize community-based norm activation, incorporate symbolic recognition features to engage egoistic motivations, and strengthen institutional trust through transparent fund reporting. This research contributes to prosocial behavior literature by empirically validating an integrative VBN-TPB model in a non-Western, high-collectivism context and provides actionable foundations for philanthropy platform developers and policymakers in Indonesia.